The influence of Organizational Citizenship Behavior and Organizational Commitment on Employee Performance at Bank Rakyat Indonesia Kantor Cabang Manado Boulevard - Bawawa, Belindah; Rumawas, Wehelmina; Mukuan, Danny D. S. (Productivity, 2024)
This research was carried out with the aim of finding out whether there is an influence between organizational citizenship behavior and organizational commitment on the performance of PT employees. Bank Rakyat Indonesia Mando Boulevard Branch Office. This research uses quantitative methods, with a sample of 30 respondents. The sampling technique in this research was carried out using a Non-probability sampling technique. Data collection in this research was carried out using a questionnaire. Data was collected and analyzed using the SEM (Structural Equation Modeling) model using the SmartPLS 4 program. Statistical test results found that Organizational Citizenship Behavior had no and significant negative effect on Employee Performance. Organizational Citizenship Behavior has a positive and significant effect on Organizational Commitment and Organizational Commitment has a positive and significant effect on Employee Performance. Thus, PT. Bank Rakyat Indonesia Manado Bouleard Branch Office must pay attention to Organizational Citizenship and Organizational Commitment within the company to further improve Employee Performance.